The influence of personal attributes and organizational ethics position on accountants' judgments: Malaysian scenario - Mohd Ghazali, Nazli Anum; Ismail, Suhaiza (Emerald Group Publishing Limited, 2013)
Purpose – The objective of this paper is to examine the influence of personal attributes, organizational ethics position and other factors which are rules conformance, active participation in profession activities, ethics instructions received and understanding of the professional code of conduct on the Malaysian accountants’ judgment on questionable ethical scenarios. Design/methodology/approach – A survey questionnaire is carried out to elicit opinions of Malaysian accountants on factors influencing ethical judgments. Findings – Adopting 15 vignettes used in Emerson et al. to assess ethical judgments, the main findings revealed from the analysis are that older accountants, accountants attached to corporations with higher ethics scale and accountants who understand the professional code of conduct are expected to be stricter in judging questionable ethical situations. Practical implications – The findings imply that perhaps one way to promote and preserve ethical organizational decisions is by employing older and experienced individuals and perhaps retaining older staff. The finding on age appears to suggest that wisdom comes with maturity. Originality/value – This paper is one of the few studies which investigate factors influencing ethical judgments of accountants in Malaysia. The research is timely given the growing importance of women in decision-making levels, the expected rise in employment and the requirement to include the business ethics course in the accounting programs in Malaysia.